SOCIAL NETWORK ANALYSIS OF AUDIENCEADJACENCY OF POLITICAL SAINT-PETERSBURG ONLINE-COMMUNITIES IN SOCIAL NET "VKONTAKTE" - Sergei Igorevich Suslov (Современная наука и инновации, 2022)
The work presents a creation of the weighted graph mathematical model of Saint-Petersburg political online-communities in popular Russian social network "VKontakte". The centrality metrics analysis and clustering analysis to search out the subgraphs was also carried out.